Literature and therapy : a systemic view - Burns, Liz (Elizabeth Irene) (Karnac, 2009)
"Literature and Therapy: A Systemic View" is an invitation to the world of literature, drawing us into the creative and imaginative spaces which lie between readers and their choice of novels, plays and poems. In this world, the fundamental importance of emotion and intuition is recognised, as is the power of literature to promote transformations of meaning in every day life and in therapeutic practice. Its potential to contribute depth and diversity to therapists' personal/professional development is explored via literary reflections and qualitative research findings. Liz Burns defines the te.